Carbon-fiber reinforced PEEK instrumentation for spondylodiscitis: a single center experience on safety and efficacy - Ann-Kathrin Joerger (Nature Portfolio, 2021)
Abstract Radiolucent carbon-fiber-reinforced (CFR) polyethyl-ether-ether-ketone (PEEK) has been established in spinal instrumentation for oncological reasons. Laboratory data reported comparable bacterial adhesion as titanium. Thus, using of CFR-PEEK spinal instrumentation for spondylodiscitis bases on artifact-free imaging to evaluate therapeutic success. Studies comparing the rate of pedicle screw loosening and relapse of spondylodiscitis following titanium versus CFR-PEEK instrumentation do not exist so far. This study evaluates the rate of pedicle screw loosening and recurrence of spondylodiscitis after CFR-PEEK instrumentation for spondylodiscitis compared to titanium. We conducted a prospective single center study between June 2018 and March 2019 on consecutive 23 patients with thoracolumbar spondylodiscitis. Imaging data was evaluated for screw loosening at a minimum of three months after surgery. A matched-pair analysis was performed using spondylodiscitis cases between 2014 and 2016 using titanium instrumentation for equal localization, surgery, and microorganism class. Among 17 cases with follow-up imaging, six cases (35%) showed screw loosening while only 14% (two patients) with titanium instrumentation were loosened (p = 0.004). In both groups the most frequent bacterium was Staphylococcus aureus, followed by Staphylococcus epidermidis. From the S. aureus cases, one infection in both groups was caused by methicillin resistant species (MRSA). No difference was found in the rate of 360° fusion in either group due to matching criteria. As opposed to other indications CFR-PEEK screws show more loosening than titanium in this series with two potentially underlying reasons: a probably stronger bacterial adhesion on CFR-PEEK in vivo as shown by a statistical trend in vitro and instrumentation of spondylytic vertebrae. Until these factors are validated, we advise caution when implanting CFR-PEEK screws in infectious cases.